THE DEVELOPMENT OF FLIPBOOK-BASED DIGITAL COMIC MEDIA ON THE 5 JANUARY 1949 BLOODY RENGAT INCIDENT AS A LOCAL HISTORY LEARNING MEDIUM: Pengembangan Media Komik Digital Berbasis Flipbook Pada Materi Peristiwa Rengat Berdarah 5 Januari 1949 Sebagai Media Ajar Sejarah Lokal - Tata Della Pratiwi; Isjoni; Asyrul Fikri (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aimed to develop a digital comic based on Flipbook technology for teaching the local history topic of the Rengat Bloody Incident on January 5, 1949. The research was motivated by the limited use of innovative digital learning media in history education, which often causes students to lose interest and experience difficulties in understanding local historical events. This research employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The study was conducted at SMAN 1 Rengat involving history teachers, media experts, material experts, and students of class XI.5 as research subjects. Data were collected through observation, interviews, questionnaires, and pre-test and post-test instruments. The results showed that the digital comic Flipbook media was categorized as highly feasible based on expert validation results from both media and material validators. In addition, the implementation results indicated that the media effectively improved students’ motivation, understanding, and learning outcomes in local history learning. The novelty of this research lies in the integration of local historical content with interactive Flipbook-based digital comics that are accessible through digital devices and designed according to students’ learning characteristics in the digital era. Therefore, the developed media can serve as an innovative and engaging learning resource for history education.